Pre-clinical evaluation of the mechanical properties of a low-stiffness cement-injectable hip stem. (17th November 2017) - Eldesouky, Ibrahim; Harrysson, Ola; Marcellin-Little, Denis J.; West, Harvey; El-Hofy, Hassan
Abstract: In total hip arthroplasty (THA), the femoral stem can be fixed with or without bone cement. Cementless stem fixation is recommended for young and active patients as it eliminates the risk of loss of fixation at the bone–cement and cement–implant interfaces. Cementless fixation, however, suffers from a relatively high early revision rate. In the current research, a novel low-stiffness hip stem was designed, fabricated and tested. The stem design provided the option to inject biodegradable bone cement that could enhance initial stem stability. The stem was made of Ti6Al4V alloy. The proximal portion of the stem was porous, with cubic cells. The stem was fabricated using electron beam melting (EBM) technology and tested in compression and bending. Finite-element analysis was used to evaluate stem performance under a dynamic load representing a stair descending cycle and compare it to the performance of a solid stem with similar geometry. The von Mises stresses and maximum principal strains generated within the bone increased after porous stem insertion compared to solid stem insertion. The low-modulus stem tested in this study has acceptable mechanical properties and generates strain patterns in bone that appear compatible with clinical use.